Optimasi Formula Sari Edamame dengan Proses Pasteurisasi Berdasarkan Karakteristik Kimia dan Sensori - Rizaludin Nur; Hanifah Nuryani Lioe; Nurheni Sri Palupi; Budi Nurtama (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2018)
Edamame is a type of white soybeans from Japan but has been cultivated in Indonesia. It is commonly harvested as immature green soybeans. One of its products is edamame milk. This research is aimed to determine the optimized condition for edamame milk formula in terms of isoflavones, total phenolics, antioxidant activity and sensory characteristics (color, taste, aroma and overall) and to verify the optimized formula at optimum conditions according to the suggested result. The research was conducted in four stages. At 1st stage, pasteurization process at 72⁰C for 15 seconds was selected for edamame milk formula, based on hedonic test result. Optimization at the second step indicated that the optimum formula obtained was 1:6 ratio edamame:water and 0.20% food additive concentration for emulsifier and stabilizer. At the third stage, the verification results showed the product had matched with the prediction values: antioxidant activity at 1.61 mg ascorbic acid/100g, isoflavone content at 41.94 µg/g, total phenolics at 99.92 mg GAE/100 mL and acceptable organoleptic properties (scale 1-7) which gave color at 5.88, taste at 4.69, aroma at 5.36 overall at 5.23. At the four stage, comparison with commercial soybean milks, exhibited that edamame milk had higher content of antioxidant activity, isoflavones and total phenolics.